The Secondary Market of Natural Gas. Operation and Aspects to be Implemented to Achieve an Efficient Market - Pomatailla Gálvez, Fernando (2015)
This article describes the creation and operation of a market that has been functioning since very recently in the country. It shows the stages for the implementation of this market, which begins with bilateral agreements to sell natural gas and transportation capacity between the actors involved, and later gives way to day-to-day electronic auctions. Additionally, this article shows the main contractual provisions which are often incorporated into bilateral agreements for the transference of transportation capacity. Finally, two important deficiencies that appeared in these years of operation will be analyzed, such as the restrictionon the transference of volumes of natural gas, and the exclusion from this market of capacity surpluses of the service of distribution of natural gas through pipelines that is contracted by consumers.